2019
DOI: 10.1021/acs.analchem.9b00913
|View full text |Cite
|
Sign up to set email alerts
|

A New Label-Free Approach to Glioblastoma Cancer Stem Cell Sorting and Detection

Abstract: Cancer stem cells (CSCs) play critical roles in cancer, making them important targets for new diagnostic and therapeutic approaches. Since CSCs are heterogeneous and not abundant in tumors, and few specific markers for these cells currently exist, new methods to isolate and characterize them are required. To address this issue, we developed a new label-free methodology to isolate, enrich, and identify CSCs from an heterogeneous tumor cell subpopulation using a cell sorting method (sedimentation field flow frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…Thus, larger and less dense cells generating more hydrodynamic lift forces within the mobile phase and not very sensitive to centrifugal force (blue cells on Figure 5A ), will be eluted before smaller and denser cells (red cells, Figure 5A ) generating less hydrodynamic forces and more sensitive to the multigravitational field. As for a number of other cell models [ 27 , 29 , 31 ], we found that under the elution conditions, U87 cells were eluted under the hyperlayer elution mode [ 28 , 30 ] schematized in Figure 5A .…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Thus, larger and less dense cells generating more hydrodynamic lift forces within the mobile phase and not very sensitive to centrifugal force (blue cells on Figure 5A ), will be eluted before smaller and denser cells (red cells, Figure 5A ) generating less hydrodynamic forces and more sensitive to the multigravitational field. As for a number of other cell models [ 27 , 29 , 31 ], we found that under the elution conditions, U87 cells were eluted under the hyperlayer elution mode [ 28 , 30 ] schematized in Figure 5A .…”
Section: Resultsmentioning
confidence: 77%
“…In each case, we observed the classical two-peak profile ( Figure 5B ); the first peak corresponds to the void peak (VP, t 0 /t 0 = R obs ≈ 1) containing unretained species (cell debris, proteins, cell aggregates…), and the second corresponds to the cell peak (CP, t 0 /t r = R obs < 1). These broad cell peaks ( Figure 5B ) correspond to very polydisperse populations, reflecting the heterogeneity of these GB cell lines containing a cell continuum, from fully differentiated cells to cancer stem cells [ 28 , 30 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, rarer, more aggressive cells still end up lost within the dynamic range. Either label-free cell sorting technologies 120 or co-staining protocols coupled to image analysis and detection algorithms may improve the specific detection of rare cells at any relevant step of the CSRA workflow. Circulating tumour cells remain easily accessible and represent a target of choice in that regard.…”
Section: Expanding the Field Of Functional Assaysmentioning
confidence: 99%
“…One of the most interesting label-free cell sorting methods is the now well-known sedimentation field-flow fractionation (SdFFF) technique. [22][23][24] . The SdFFF is a gentle and noninvasive technique.…”
Section: Introductionmentioning
confidence: 99%